2015
DOI: 10.1515/nuka-2015-0121
|View full text |Cite
|
Sign up to set email alerts
|

A study of cerium extraction by TBP and TODGA using a rotating diffusion cell

Abstract: Abstract. For the study of the coupled interfacial-mass transfer kinetics of, inter alia, TBP, TODGA, CyMe 4 -BTBP and CyMe 4 -BTPhen based solvent extraction processes, a new rotating diffusion cell (RDC) apparatus has been established at Lancaster University. RDC studies of Ce(IV)/TBP and Ce(III)/TODGA extraction systems have been undertaken in order to improve the understanding of the chemical and kinetic processes involved. In each case, an interesting dependency on local hydrodynamics at the solution phas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 8 publications
(9 reference statements)
0
3
0
Order By: Relevance
“…The absorbance of the yellow complex was followed at a constant temperature in the dark at 325 nm (ε = 3930 L mol –1 cm –1 ). The wavelength is in good agreement with that in Bromley and Boxall studies …”
Section: Experimental Sectionmentioning
confidence: 99%
See 1 more Smart Citation
“…The absorbance of the yellow complex was followed at a constant temperature in the dark at 325 nm (ε = 3930 L mol –1 cm –1 ). The wavelength is in good agreement with that in Bromley and Boxall studies …”
Section: Experimental Sectionmentioning
confidence: 99%
“…The wavelength is in good agreement with that in Bromley and Boxall studies. 46 Infrared Spectroscopy. Infrared spectra (see Supporting Information) were measured on a PerkinElmer Spectrum Two spectrometer between 4000 and 400 cm −1 , equipped with a diamond attenuated total reflectance accessory.…”
Section: ■ Conclusionmentioning
confidence: 99%
“…Through use of this technique, we have quantified the interfacial kinetics of the extraction of Ce(III) by TODGA [4] and have identified that the key complexation reaction takes place in the aqueous solution phase [5]. Further observations have shown the rate of Ce extraction to have linear dependence on the aqueous concentrations of both Ce(III) and HNO3 (not shown), indicating that the extraction process occurs with the inclusion of a single nitrate ion in the first coordination sphere of the Ce(III)-TODGA complex; and, through variation of both hydrodynamic conditions and key solution concentrations, that the system operates under mixed mass transfer with chemical reaction (MTWCR) control [6].…”
Section: Introductionmentioning
confidence: 99%